Bond-stress and bar-strain profiles in RC tension members modelled via finite elements. (1st September 2019) - Jakubovskis, Ronaldas; Kaklauskas, Gintaris
Graphical abstract: Highlights: Mechanics of bond is studied numerically. Three numerical approaches are validated on the measured reinforcement strain profile. 3D rib-scale modelling technique enables to simulate deterioration of bond. Abstract: Concrete-reinforcement interaction is a complex issue in the mechanics of reinforced-concrete structures all the more because the reinforcement, the concrete layer at the interface and the undamaged concrete are involved. With reference to the modelling of short tension members embedded in the concrete, three alternative approaches are considered in this paper: a two-dimensional rib-scale approach ( Model-1 ); a three-dimensional approach with the simplified representation of the ribs ( Model-2 ); and a three-dimensional rib-scale approach ( Model-3 ). The effectiveness of each approach is checked against the results yielded by a number of tests on RC prisms in tension reinforced with a single bar, where the strain distribution in the bar was measured. Special attention is devoted to bond deterioration close to the cracks. The three-dimensional rib-scale model is shown to be effective in describing the strain profiles in the reinforcement at different load levels, and rib height appears to be the most important parameter governing the calibration of the model. In addition, the role played by the net cover of the bar is thoroughly investigated.